Acute biliary pancreatitis: a prospective observational hospital-based study - Kodliwadmath, Harsha B.; Srinivas Pai, B.; Ubarale, Manasa (International Surgery Journal, 2020)
Background: Acute biliary pancreatitis (ABP) is one of the most serious complications of gall stone disease with a high risk of morbidity and mortality. Hence accurate diagnosis and prompt management of ABP is very crucial. Different management strategies exist regarding indications and timing for interventions, endoscopic retrograde cholangio-pancreaticography (ERCP) and cholecystectomy. Methods: Ours is a prospective observational study of the different clinical presentations and management strategies and their respective outcomes in our hospital. All cases of ABP admitted over a period of one year were included in the study. The clinical presentation, severity and course of the disease, imaging studies, duration of ICU and hospital stay and timing of ERCP and cholecystectomy were studied. Results: A total of 56 cases were included in the study. Average age was 45 years. Pain abdomen was the most common symptom at presentation. About 82% patients had mild to moderate disease while the rest had severe disease. The mean duration of intensive care unit stay was 8 days. ERCP was done in 6 cases. Cholecystectomy during the same admission was dine in 20 cases. There were 2 deaths during the course of the study. Conclusions: Early intervention definitely reduces morbidity, mortality and recurrent admissions in cases of acute biliary pancreatitis. Same admission laparoscopic cholecystectomy is preferable in mild ABP. All cases of severe ABP must undergo early ERCP irrespective of biliary obstruction. This also helps in reducing readmissions due to pancreatic-biliary complications and is cost-effective.